A Multicenter Pilot Study Assessing Regional Cerebral Oxygen Desaturation Frequency During Cardiopulmonary Bypass and Responsiveness to an Intervention Algorithm. (June 2016) - Subramanian, Balachundhar; Nyman, Charles; Fritock, Maria; Klinger, Rebecca Y.; Sniecinski, Roman; Roman, Philip; Huffmyer, Julie; Parish, Michelle; Yenokyan, Gayane; Hogue, Charles W.
Abstract : BACKGROUND: The purpose of this multicenter pilot study was to: (1) determine the frequency of regional cerebral oxygen saturation (rScO2 ) desaturations during cardiac surgery involving cardiopulmonary bypass (CPB); (2) evaluate the accuracy of clinician-identified rScO2 desaturations compared with those recorded continuously during surgery by the near-infrared spectroscopy (NIRS) monitor; and (3) assess the effectiveness of an intervention algorithm for reversing rScO2 desaturations. METHODS: Two hundred thirty-five patients undergoing coronary artery bypass graft and/or valvular surgery were enrolled at 8 US centers in this prospective observational study. NIRS (Invos™ 5100C; Covidien) was used to monitor rScO2 during surgery. The frequency and magnitude of rScO2 decrements >20% from preanesthesia baseline were documented, and the efficacy of a standard treatment algorithm for correcting rScO2 was determined. The data from the NIRS monitor were downloaded at the conclusion of surgery and sent to the coordinating center where the number of clinician-identified rScO2 desaturation events was compared with the number detected by the NIRS monitor. RESULTS: The average rScO2 obtained at baseline (mean ± SD, 61% ± 11%; 99% confidence interval, 57%–65%) and during CPB (62% ± 14%; 57%–67%) was not different. However, rScO2 after separation from CPB (56% ± 11%; 53%–60%) was lower than measurements at baseline and during CPB ( P < 0.001). During CPB, rScO2 desaturations occurred in 61% (99% confidence interval, 50%–75%) of patients. The area under the curve for product of magnitude and duration of the rScO2 was (mean ± SD, 145.2; 384.8% × min). Clinicians identified all patients with an rScO2 desaturation but identified only 340 (89.5%) of the 380 total desaturation events. Of the 340 clinician-identified rScO2 desaturation events, 115 resolved with usual clinical care before implementation of the treatment algorithm. For the remaining 225 events, the treatment algorithm resulted in resolution of the rScO2 desaturation in all but 18 patients. CONCLUSIONS: This multicenter pilot study found that 50% to 75% of patients undergoing cardiac surgery experience one or more rScO2 desaturations during CPB. Nearly 10% of desaturation events were not identified by clinicians, suggesting that appropriate alarming systems should be adopted to alert clinicians of such events. The intervention algorithm was effective in reversing clinically identified rScO2 desaturations in the majority of events. Abstract : Supplemental Digital Content is available in the text.Published ahead of print March 29, 2016